DEVICE FOR STUDY OF DYNAMIC SURFACE TENSION OF AQUEOUS SURFACTANT SOLUTIONS - Kisil, Igor; Bilischuk, Victor; Kuchirka, Yuriy; Barna, Olga (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
Theoretical bases of fixed spinning drop method for the study of dynamic interfacial tension of aqueous surfactant solutions on the border with other immiscible liquids in water are considered. The block diagram and appearance of the device, which implements the method of fixed spinning drop are given. There are provided the results of research of the dynamic interfacial tension between the base oil and aqueous solutions of surfactants Tipol and Savenol of different concentrations used for intensification of oil and gas extraction.